Halal Tourism: Its Attractiveness to Domestic Tourists Based on Their Religious Perspectives - Ambara Purusottama; Gregorius Dimas Hapsoro Prastowo (Program Pascasarjana, 2019)
One of Indonesia’s government programs to boost tourism as the basis of Indonesia’s economy is Halal tourism. This study aimed at exploring the behavior of domestic Muslim tourists when considering halal tourist destinations. It also looked at Muslim tourists’ behavior as they selected and recommended halal tourist destinations and compared the results according to the degree of taqwa in performing their religious rituals. This study used judgmental sampling in the selection of respondents and successfully collected 511 valid questionnaires. The theory of planned behavior (TPB) was used to analyze the study subjects, namely domestic Muslim tourists when they intended to select and recommend halal tourist destinations. It revealed that when domestic Muslim tourists intended to select and recommend halal tourist destinations, they influenced by Behavior Control. Attitude and Subjective norm did not influence the intention to select and recommend halal tourist destinations. Moreover, there was an adverse relationship between Attitude and Subjective Norm in the intention. The result of this study may contribute to the behavior theory and expand the use of TPB in the field of halal tourism study.Keywords: degree of taqwa, domestic tourists, halal tourist destinations, theory of planned behavior.